Pengaruh Pemberian Kredit terhadap Profitabilitas pada PT. Bank Sumut - Butar, Juwita Riama Anzelina Butar; Sijabat, Jadongan; Gaol, Manatap Berliana Lumban (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of lending on profitability at PT. Bank sumut, Jl. Imam bonjol No.18. The population in this study is the financial statements of PT. Bank North Sumatra during 2013-2022, and the sample in this study is the Quarterly data of PT. Bank sumut so that the number of samples produced as much as 40. The data used in this study is secondary data taken by documentation method by accessing banksumut website. The data analysis method uses statistical analysis with descriptive statistical testing, simple regression testing, correlation, hypothesis testing and determination, with the statistical tool used is SPSS 26. The results showed that the provision of credit had a negative and significant effect on profitability A negative t value indicates that the variable of lending (X) has an influence that is not in line with profitability (Y). So it can be concluded that the provision of Credit (X) has a negative influence on Profitability (Y) and is significant. That is, the greater the provision of credit will result in the acquisition of the profitability ratio of PT. Bank North Sumatra decreases, on the other hand, if lending decreases, there will be an increase in profitability at PT. North Sumatra Bank. This is due to the lack of banks in applying the principle of prudence in lending resulting in non-performing loans, so banks are advised to maintain the principle of prudence in providing credit to minimize credit risk and maximize company profitability.